2018
DOI: 10.5812/archcid.63121
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic or Antagonistic Effects of Probiotics and Antibiotics- Alone or in Combination- on Antimicrobial-Resistant Pseudomonas aeruginosa Isolated from Burn Wounds

Abstract: Background: Bacterial burn infections are one of the serious infections and since their treatment with antibiotics is very difficult, infection control in such wounds is very important. Therefore, methods should be sought to enhance the effects of antibiotics and also reduce the resistance to them. It seems that probiotics have antimicrobial features and are effective in wound healing. Objectives: The current study aimed at evaluating and comparing the antimicrobial effects of antibiotics and probiotics, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Four studies included supernatants or extracts produced by probiotic strains [67,69,71,74], whilst the other studies used live probiotic cultures. Eight studies included various monospecies probiotics, whilst six studies included multispecies probiotics [64,66,70,71,73,75]. Two studies from Table 1 [61,68] also included animal model experiments and are additionally noted in Table 2.…”
Section: In Vitro Studies On the Use Of Probiotics For Woundmentioning
confidence: 99%
“…Four studies included supernatants or extracts produced by probiotic strains [67,69,71,74], whilst the other studies used live probiotic cultures. Eight studies included various monospecies probiotics, whilst six studies included multispecies probiotics [64,66,70,71,73,75]. Two studies from Table 1 [61,68] also included animal model experiments and are additionally noted in Table 2.…”
Section: In Vitro Studies On the Use Of Probiotics For Woundmentioning
confidence: 99%
“…and ciprofloxacin against P. aeruginosa growth. Similarly, [31] showed in their study that there was a synergistic effect between antibiotics and probiotics. The synergistic reaction of Lactobacillus and antibiotics enhancing their antibacterial properties and restores its ability to destroy bacteria that have acquired resistance to it [32].…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 87%
“…Substances metabolized by these strains may have the potential to act synergistically with antibiotics. In vitro experiments have shown that the combination of tetracycline and probiotic fermentation broth has greater antimicrobial effects against Pseudomonas aeruginosa clinical resistant strains than either tetracycline or probiotic fermentation broth does alone [94]. Yang et al conducted an antibacterial study on Clostridium difficile, and the results showed that Bifidobacterium breve YH68 cell-free supernatant can enhance the synergistic effect of antibiotics and weaken the antagonistic effect [95].…”
Section: Drug Synergy and Mutant Prevention Theoriesmentioning
confidence: 99%